2016
DOI: 10.1109/tcomm.2016.2565580
|View full text |Cite
|
Sign up to set email alerts
|

Secrecy Capacity Analysis Over $\kappa $ – $\mu $ Fading Channels: Theory and Applications

Abstract: In this paper, we consider the transmission of confidential information over a κ-µ fading channel in the presence of an eavesdropper, who also observes κ-µ fading. In particular, we obtain novel analytical solutions for the probability of strictly positive secrecy capacity (SPSC) and the lower bound of secure outage probability (SOP L ) for channel coefficients that are positive, real, independent and non-identically distributed (i.n.i.d.). We also provide a closed-form expression for the probability of SPSC w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
88
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 34 publications
(48 reference statements)
1
88
0
Order By: Relevance
“…Additionally, it has been shown that double Rayleigh distribution also fits various measurements in different suburban outdoor-to-indoor mobile-to-mobile (M2M) communication scenarios as well as for keyhole channels [12]. Motivated by the latest advances in physical layer security analysis [2]- [6] and the importance of security in vehicular communications, we study the secrecy performance of vehicular communications in this letter. Additionally, due to the high mobility of vehicles, and more importantly, the eavesdropper's intention to hide its position, we also take into account of the uncertainty of the eavesdropper's location in our analysis.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Additionally, it has been shown that double Rayleigh distribution also fits various measurements in different suburban outdoor-to-indoor mobile-to-mobile (M2M) communication scenarios as well as for keyhole channels [12]. Motivated by the latest advances in physical layer security analysis [2]- [6] and the importance of security in vehicular communications, we study the secrecy performance of vehicular communications in this letter. Additionally, due to the high mobility of vehicles, and more importantly, the eavesdropper's intention to hide its position, we also take into account of the uncertainty of the eavesdropper's location in our analysis.…”
Section: Introductionmentioning
confidence: 87%
“…There is an increasing number of research exploring the physical layer secrecy performance of communication systems over different fading conditions. The average secrecy capacity (ASC) over κ-µ and α-µ fading channels have been derived in [2] and [3], respectively. The secrecy outage probability (SOP) performance over correlated composite Nakagami-m/Gamma fading channels was investigated in [4].…”
Section: Introductionmentioning
confidence: 99%
“…The main contributions of this letter are as follows: 1) A novel series based expression for the average secrecy capacity (ASC) is derived in terms of the extended generalized bivariate Fox H function (EGBFHF) for the classical Wyner's model [12] under the α-η-κ-µ fading. 2) Exact and generalized expression is obtained for the secrecy outage probability (SOP) in terms of the Meijer G function contrary to previous works [2], [13], [14], where only lower bound of SOP is derived. The strictly positive secrecy capacity (SPSC) can be obtained from the derived SOP by setting the target secrecy rate to zero.…”
Section: Introductionmentioning
confidence: 88%
“…In this case, the instantaneous secrecy capacity of the considered system is defined as C s (γ B , γ E ) = max{ln(1 + γ B ) − ln(1 + γ E ), 0} [2]. The ASC, C s , can be obtained from [2] C…”
Section: Secrecy Performance Analysis a Asc Analysismentioning
confidence: 99%
See 1 more Smart Citation